2013
DOI: 10.1038/bjc.2013.705
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between cell-free DNA and tumour burden was estimated by PET/CT in patients with advanced NSCLC

Abstract: Background:Cell-free DNA (cfDNA) circulating in the blood holds a possible prognostic value in malignant diseases. Under malignant conditions, the level of cfDNA increases but the biological mechanism remains to be fully understood. We aimed to examine the correlation between cfDNA and total tumour burden defined by positron emission tomography (PET) parameters.Methods:Patients with advanced non-small cell lung cancer (NSCLC) were enrolled into a prospective biomarker trial. Before treatment, plasma was extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 30 publications
3
79
2
Order By: Relevance
“…Nevertheless, it is the first time, to our knowledge, that this parameter has been studied simultaneously on two different genes by targeting either a KRAS or a BRAF WT sequence highlighting the robustness of our analytic process and the robustness of the prognostic significance of total ccfDNA concentration. Previous observations of our group on xenografted mice have shown the strong correlation between tumor volume and ccfDNA concentration (33), and other works have showed that ccfDNA concentration is positively correlated to tumor burden (7,28,34). Spindler and colleagues (8) revealed the correlation between the concentration of mutant ccfDNA (mA) and OS.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, it is the first time, to our knowledge, that this parameter has been studied simultaneously on two different genes by targeting either a KRAS or a BRAF WT sequence highlighting the robustness of our analytic process and the robustness of the prognostic significance of total ccfDNA concentration. Previous observations of our group on xenografted mice have shown the strong correlation between tumor volume and ccfDNA concentration (33), and other works have showed that ccfDNA concentration is positively correlated to tumor burden (7,28,34). Spindler and colleagues (8) revealed the correlation between the concentration of mutant ccfDNA (mA) and OS.…”
Section: Discussionmentioning
confidence: 81%
“…Tumor cells release ccfDNA, which exhibits the genetic and epigenetic alterations of the tumor of origin (4). The clinical significance of tumor-derived ccfDNA released in the blood of patients with colorectal cancer has already been investigated as a prognostic tool in previous studies using various technologic approaches (5)(6)(7)(8)(9). In a recent large meta-analysis, a high correlation between ccfDNA concentration and mCRC patient survival was observed, revealing that patients with relatively low levels of ccfDNA lived significantly longer than patients with higher levels (6).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Morelli et al recently measured the sums of lesion volumes measured (manually on each image, by three independent readers in a total of 23 patients), but found no significant correlation between tumor volume and percentage of acquired mutant reads in the plasma [78]. In a Danish group of patients with mCRC, both total cfDNA and mutated DNA were analyzed in relation to positron emission tomography-computed tomography (PET-CT) parameters similar to a study published in lung cancer [79]. Data revealed a weak correlation to quantitative measures of both total and mutated DNA [33].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that higher pretreatment ctDNA levels were associated with worse OS in patients who were treated with first-line platinum doublet chemotherapy (16.8 vs. 22.4 months) (15). In another report, increased plasma ctDNA levels were correlated with advanced tumor stage, tumor progression after chemotherapy as well as poor survival (16,17).…”
Section: Circulating (Cell-free) Tumor Dna (Ctdna)mentioning
confidence: 99%